A lipase based approach to understand the role of wheat endogenous lipids in bread crumb firmness evolution during storage. Issue 2 (December 2015) - Gerits, Lien R.; Pareyt, Bram; Masure, Hanne G.; Delcour, Jan A.
Abstract When forming amylose-lipid (AM-L) inclusion complexes, surfactants retard bread crumb firming. Some wheat endogenous lipids have structures similar to those of surfactants. Lipase use in bread making increases the level of free fatty acids and 'lyso' lipids which can form AM-L complexes. We here used three lipases (Lipopan F, Lecitase Ultra, and Lipolase) with different specificities and the surfactant sodium stearoyl lactylate (SSL) for studying the role of lipids in bread crumb firmness and storage induced crumb firming. The lipases and SSL similarly impacted bread crumb texture. Their use induced less pronounced crumb firmness and stiffness increases as well as a less pronounced decrease in resilience than in control bread loaves. Amylopectin (AP) retrogradation was slower but in the end proceeded to a similar extent, as noted with low-field nuclear magnetic resonance. Differences in AP retrogradation after 7 days of storage (as observed with Lipolase) were attributed to the location and type of lipids hydrolysed by the respective lipase enzymes. Lipase hydrolysis products originating from lipids in the free lipid fraction probably had more impact on AP retrogradation than the free fatty acids and 'lyso' lipids obtained by hydrolysis of lipids 'bound' to the gluten network.